(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Due to the remote classes as a result of the pandemic, it became evident the increase in the use of cell phones in students, this brought with it alterations in the behavior of students and psychological consequences such as the development of stress, anxiety, depression, among others. However, these effects do not develop to the same extent in all individuals since factors such as personality influence them. Thus, the present study aimed to determine the relationship between personality and nomophobia in virtual education students in the context of the pandemic. The research was of basic type, with an explanatory level, non-experimental, causal correlational design. The population was 328 students and the sample consisted of 104 students. The instruments used were: the nomophobia questionnaire NMP-Q (20 items) and the Eysenck personality inventory (49 items). According to the results obtained, the relationship index between personality and nomophobia is 0.815, and there is a significance of 0.000, which is less than 0.05, so the null hypothesis is rejected, concluding that personality and nomophobia are related in a high significant way.